2016
DOI: 10.37341/interest.v5i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Senam Yoga Dengan Kesiapan Fisik Dan Psikologis Ibu Hamil Dalam Menghadapi Persalinan Di Kelas Antepartum Gentle Yoga Yogyakarta

Abstract: Yoga in Pregnant, Physical and Psychological Of Preparation. During pregnancy will change physically and psychologically that will be experienced by a mother. These changes may cause discomfort, especially in the third trimester. Therefore pregnant women should receive care in pregnancy to be able to adapt to changes both physical and psychological. The purpose of care during pregnancy to prepare for childbirth which is physiological with the aim of mother and fetus will be born in a healthy state. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
2
0
14
Order By: Relevance
“…The results showed that after being given Dhyana education in reducing anxiety in pregnant women in Oeltua village, there were Mean (17.45), Median (17.00), Standard Deviation (2.450), Maximum (20), Minimum (10). (Sari & Puspitasari, 2016) said Pregnant women already understand the meaning of Dhyana meditation, the purpose of meditation, the benefits of meditation and how to do meditation properly so that pregnant women can overcome anxiety during pregnancy by doing good and correct meditation. (Ngurah, 2001) states that practicing meditation can get used to learning to be happy at any time, in all situations, even difficult ones, gradually freeing oneself from psychological problems such as anxiety, disappointment and stress.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that after being given Dhyana education in reducing anxiety in pregnant women in Oeltua village, there were Mean (17.45), Median (17.00), Standard Deviation (2.450), Maximum (20), Minimum (10). (Sari & Puspitasari, 2016) said Pregnant women already understand the meaning of Dhyana meditation, the purpose of meditation, the benefits of meditation and how to do meditation properly so that pregnant women can overcome anxiety during pregnancy by doing good and correct meditation. (Ngurah, 2001) states that practicing meditation can get used to learning to be happy at any time, in all situations, even difficult ones, gradually freeing oneself from psychological problems such as anxiety, disappointment and stress.…”
Section: B Discussionmentioning
confidence: 99%
“…Yoga can help pregnant women to prepare physically and psychologically during childbirth, this is evidenced by research conducted by (Sari & Puspitasari, 2016), there is a significant relationship (p <0.001) between yoga sports on the physical and psychological preparation of pregnant women during labor (Sari & Puspitasari, 2016).…”
Section: Introductorymentioning
confidence: 99%
“…Berdasarkan kategori umur, hasil penelitian ini sama seperti hasil penelitian yang dilakukan di Yogyakarta yang menunjukkan sebagian besar ibu berumur antara 20-27 tahun (54,6%). Penelitian tersebut menunjukkan adanya hubungan yang bermakna antara umur ibu dengan kesiapan dalam menghadapi persalinan (Sari & Puspitasari, 2016). Kategori umur ini merupakan usia reproduktif bagi wanita.…”
Section: Karakteristi Respondenunclassified
“…Berbeda dengan hasil penelitian ini, penelitian yang dilakukan oleh Sari & Puspitasari (2016) dimana pada hasil penelitian tersebut Sebagian besar responden yang mengikuti kelas ibu hamil adalah pada kelompok paritas Primigravida (79,2%). Terlihat perbedaan yang signifikan pada kelompok paritas primigravida untuk kesiapan dalam menghadapi persalinan yang dapat dipengaruhi oleh rasa keingintahuan ibu primigravida dalam mengikuti kelas antenatal.…”
Section: Karakteristi Respondenunclassified
“…7 Begitupun hasil penelitian Sari kebanyakan responden memiliki riwayat paritas nullipara sebesar 79,2%. 14 Pendidikan terakhir pada penelitian ini menunjukkan bahwa kebanyakan responden memiliki pendidikan yang tinggi, yaitu sebesar 60,8% untuk tingkat SMA dan PT. Penelitian ini sejalan dengan hasil yang diperoleh Rusmita kebanyakan responden memiliki pendidikan yang tinggi, yaitu SMA dan PT sebesar 96,9%.…”
Section: Pendahuluanunclassified